Productivity Improvement Onion Plants (Allium ascalonicum L) With The Use Of Liquid Organic Fertilizer Water Hyacinth and Potassium Nitrate (KNO3) - Ernita Ernita; M. Nur; Nadya Puspita (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Shallots (Allium ascalonicum L) is an important vegetable plant as a kitchen spice. and as traditional medicine. The productivity of shallots in Riau is still low, due to low soil fertility. For this reason, fertilization is carried out by combining liquid organic fertilizer with water hyacinth and potassium nitrate (KNO3). The aim of this study was to determine the main interaction and influence of POC Water Hyacinth and KNO3 on the growth and production of shallots. The research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of Riau from August 2020 to November 2021. The design used was a 4 x 4 Factorial Completely Randomized Design with 3 replications. The first factor is the concentration of water hyacinth POC consisting of 4 levels, namely 0, 100, 200 and 300 ml per liter of water. The second factor was KNO3 consisting of 4 levels, namely 0, 15, 30 and 45 g per plot. Parameters observed were plant height, harvest age, number of tubers per clump, wet tuber weight per clump, dry tuber weight per clump, dry tuber weight per tuber and tuber loss weight. at the 5% level. The results of the study concluded that the interaction of water hyacinth POC and KNO3 had a significant effect on harvest age. The best combination of factor levels was the concentration of POC in water hyacinth 100 ml/l water and KNO3 45 g/plot. The effect of water hyacinth POC was significant on plant height, harvest age, tuber wet weight per clump, tuber dry weight per clump and dry weight per tuber. The best treatment for water hyacinth POC concentration is 200 ml/l water. The effect of KNO3 is significant on harvest age. The best treatment dose of KNO3 45 g/pl The best treatment for water hyacinth POC concentration is 200 ml/l water. The effect of KNO3 is significant on harvest age. The best treatment dose of KNO3 45 g/pl The best treatment for water hyacinth POC concentration is 200 ml/l water. The effect of KNO3 is significant on harvest age. The best treatment dose of KNO3 45 g/plot.